Influence of pressurization rate and mode on cell damage of Escherichia coli and Staphyloccocus aureus by high hydrostatic pressure - Yang, Dong; Li, Renjie; Dong, Peng; Rao, Lei; Wang, Yongtao; Liao, Xiaojun (Frontiers in Microbiology, 2023)
As a non-thermal technology, high hydrostatic pressure (HHP) has been widely investigated for inactivating microorganisms in food. Few studies have been presented on the pressurization/depressurization rate and mode of microbial inactivation. In this study, effect of pressurization rate and mode on Escherichia coli and Staphylococcus aureus cell damage during HHP treatment was investigated. The results showed that fast pressurization + linear mode (FL) treatment has the best bactericidal effect on E. coli and S. aureus, followed by fast pressurization + stepwise mode (FS) and slow pressurization + stepwise mode (SS) treatments. FL treatment caused more morphological damage to the cell wall, cell membrane, and cytoplasmic components compared with FS and SS treatment detected by SEM and TEM. Additionally, the damage to membrane permeability of them was also enhanced after FL treatment. Therefore, our results indicated that FL treatment could be applied to enhance the bactericidal effect of HHP on bacteria by increasing the damage to cell morphological structure and membrane integrity.